Diagnostic Utility of Sonography and Correlation Between Sonographic and Clinical Findings in Patients With Carpal Tunnel Syndrome. (1st November 2013) - Tajika, Tsuyoshi; Kobayashi, Tsutomu; Yamamoto, Atsushi; Kaneko, Tetsuya; Takagishi, Kenji
Abstract : Objectives: First, we investigated the accuracy of carpal tunnel syndrome diagnosis by comparing the cross‐sectional area of the median nerve measured at the level of proximal inlet of the carpal tunnel with that measured at the level of the distal radioulnar joint on sonography. Second, we evaluated the correlation between sonographic and neurophysiologic findings and clinical findings assessed by the Carpal Tunnel Syndrome Instrument of the Japanese Society for Surgery of the Hand (JSSH). Methods: Fifty wrists in 34 patients and 81 wrists in 45 healthy volunteers were examined. The proximal cross‐sectional area and the difference (Δ) between the proximal and distal cross‐sectional areas were calculated for each wrist. Nerve conduction velocity tests were performed for all patients with carpal tunnel syndrome. The proximal, distal, and Δ cross‐sectional areas were compared for the two groups. We examined the correlation between the proximal, distal, and Δ areas, nerve conduction velocity findings, and JSSH scores in the patients. Results: The diagnosis of carpal tunnel syndrome determined by the Δ cross‐sectional area was more accurate than the diagnosis determined by the proximal area on receiver operating characteristic curve analysis ( P = .006). Statistically significant correlations were found between proximal area, Δ area, and nerve conduction velocity findings (proximal, r = 0.45; P = .0013; Δ, r = 0.44; P = .001). The proximal and distal areas were positively correlated with the JSSH symptom severity score (proximal, r = 0.39; P = .005; distal, r = 0.35; P = .014). Conclusions: The cross‐sectional area method using sonography has excellent performance for diagnosing carpal tunnel syndrome. It was useful for measuring the proximal and distal cross‐sectional areas to evaluated the symptom severity and for calculating the Δ cross‐sectional area to assess motor nerve damage in patients with carpal tunnel syndrome.